(untitled) (Global Journal of Science Frontier Research, 2023)
The river Cauvery was explored from origin to confluence at BoB (into two stretches) to unravel its eco-physiography, limno-chemical profile, biotic components, pollution scenario, fish species composition, abundance and fish bio-diversity. Data thus collected was processed through different statistical tools to have conspicuous relationship with the abiotic and biotic components, productivity and the fish species. Water and sediment quality parameters revealed that the river is low productive in Karnataka stretch with increment in productivity in downstream in Tamil Nadu because of innate characters having moderate acidic basin in the upper stretch as validated by its alkalinity, hardness, water and sediment reaction (pH) getting reflected in primary productions. Most of the tributaries showed productive criteria contributing moderately to limno-chemical profiles of main Cauvery. Local pollution was not phenomenal as revealed by chloride content in some of the tributaries especially encountered with the first monsoon flood. The fish catch in the entire Cuvery system has been dwindled drastically with a great reduction in catch structure as well as faunistic diversity. The study is a modest attempt, will be of immense help in unravelling the various facets of riverine ecology and their bearing on productivity, and overall riverine eco-health.